MyFread - Mohd Azhar, Muhammad Izzul; Ismai, Nora Asyikin; Ramli, Aliya; Mohd Helmi, Mohd Firdaus (Universiti Teknologi MARA, Kedah, 2019)
People nowadays, like to see something that is incredible and can attract their interest to something that they have not seen yet. So, we come out with new technologies that was an invention from existence technology named as XXXXX (Fun & Read). It was a video display that use combination for all multimedia between image, text, video, animation and sound that appear all in one from your smartphone after we scan code from that book. XXXXX will provide functions of user reading a book through the screen but just as a real book where user can control flip the book’s screen as usual and read through the screen.